2015
DOI: 10.1007/s00253-015-7230-9
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of dibenzocyclooctadiene lignans in agar cultures and in stationary and agitated liquid cultures of Schisandra chinensis (Turcz.) Baill

Abstract: Schisandra chinensis plant in vitro cultures were maintained on Murashige and Skoog (MS) medium supplemented with 3 mg/l 6-benzyladenine (BA) and 1 mg/l 1-naphthaleneacetic acid (NAA) in an agar system and also in two different liquid systems: stationary and agitated. Liquid cultures were grown in batch (30 and 60 days) and fed-batch modes. In the methanolic extracts from lyophilized biomasses and in the media, quantification of fourteen dibenzocyclooctadiene lignans identified based on co-chromatography with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 32 publications
5
48
0
Order By: Relevance
“…Similar studies with other medicinal plant species have also revealed that the liquid media increased production of metabolites such as lignans in shoot-differentiating callus cultures of Schisandra chinensis (Szopa et al 2016) and polyphenolic compounds in the Hypericum perforatum shoot liquid culture (Savio et al 2011). The elimination of agar from the culture medium also resulted in substantial savings in cost.…”
Section: Quantification Of Flavones and Verbascoside In Multiple Shootssupporting
confidence: 61%
“…Similar studies with other medicinal plant species have also revealed that the liquid media increased production of metabolites such as lignans in shoot-differentiating callus cultures of Schisandra chinensis (Szopa et al 2016) and polyphenolic compounds in the Hypericum perforatum shoot liquid culture (Savio et al 2011). The elimination of agar from the culture medium also resulted in substantial savings in cost.…”
Section: Quantification Of Flavones and Verbascoside In Multiple Shootssupporting
confidence: 61%
“…On the same studied media variants containing the same concentrations of BA and NAA, the two different lines-shoot and callus lines of Echinocereus cinerascens-were forming and growing without a tendency to dedifferentiation or differentiation, respectively (Elias et al 2014). To date, our experiences with in vitro cultures of medicinal plants have indicated that there are some genetic preferences of different plant species to form more or less differentiating lines in the beginning, and sometimes, it is very difficult to observe visible organogenesis in callus and dedifferentiation in shoot culture lines after changing the concentrations of GRs (Szopa and Ekiert 2012;Szopa et al 2016;Ekiert et al 2014;Kubica et al 2017). Perhaps, in the in vitro cultures of studied aronias, the range of the GRs concentrations tested by us (0.1-3 mg/L) and the duration of experiment (3 × 4 weeks) were not enough to observe visible changes in the level of organogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of the concentrations of GRs on the accumulation of different biogenetic groups of plant metabolites is an eminent fact (Ramawat and Mathur 2007). It has been proven, for example, in the accumulation of anthocyanins in callus cultures of Bridelia stipularis (Sreenivas et al 2011), coumarins in callus cultures of Ammi majus (Ekiert and Gomółka 2000a) and Pastinaca sativa (Ekiert and Gomółka 2000b), secoiridoid and xanthone glycosides in shoot cultures of Gentiana dinarica (Branka et al 2013), alkaloids in suspension cultures of Solanum eleagnifolium (Alvarez et al 1993), triterpenes in callus cultures of Salvia tomentosa (Georgiev et al 2011), verbascoside in callus cultures of Verbena officinalis (Kubica et al 2017) and in the accumulation of podophyllotoxin in callus cultures of Hyptis suaveolens (Velóz et al 2013) and dibenzocyclooctadiene lignans in shoot-differentiating callus cultures of Schisandra chinensis (Szopa and Ekiert 2011;Szopa et al 2016Szopa et al , 2017b. The great influence of GRs on the production and accumulation of metabolites was also shown for PA in adventitious root cultures of Eryngium maritimum (Kikowska et al 2014), in Ruta graveolens shoot cultures of (Ekiert et al 2009), in R. g. ssp.…”
Section: Discussionmentioning
confidence: 99%
“…In in vitro cultures (shoot cultures of Ruta graveolens, shoot-differentiating callus cultures of Ruta graveolens ssp. divaricata and Schisandra chinensis) we achieved about fourfold the biomass growth increments during 4 weeks of culture cycles [19][20][21].…”
Section: Discussionmentioning
confidence: 99%